Ethnographic perspectives on the mediation of informality between people and plans in urbanising China. (May 2018) - Smart, Alan
In this introduction to some of the themes of this special issue on People and plans in urbanising China, I draw on Herbert Gans' prescient comments about the importance of informality in mediating between plans and the various groups of people, users and planners, who shape their formation and implementation. Informality is even more important in the governance of cities in China. Comparing contemporary Chinese cities with Hong Kong, I suggest that informal responses, both in society and within government, can produce significant changes in plans that may increase the effectiveness or appropriateness of urban governance. Careful ethnographic research is required, however, in order to access the subtle and non-public nature of such interactions and their consequences. This commentary draws out some of the themes from articles included in this special issue, and highlights how informality intersects with plans and the people who create them and are influenced by them.